Implementation of Indiscipline State Civil Apparatus (SCA) Development at The Bengkulu City Government - Sinario Priskianto; Suparman Suparman; Kahar Hakim (Asian Journal of Social and Humanities, 2023)
The purpose of this study is to find out and explain how the implementation of indisciplined State Civil Apparatus (ASN) coaching is carried out in the Bengkulu City Government (referring to Government Regulation Number 94 of 2021 concerning Discipline for Civil Servants) and what obstacles are found in the implementation of coaching. This type of research is qualitative with the method used is descriptive analytical. The location of this research was carried out in the Bengkulu City Government. The results of this study consist of two namely; (1) The implementation of indiscipline ASN development in the work environment of the Bengkulu city government is appropriate and refers to PP No. 94 of 2021, although there are several cases that still use PP No. 53 of 2010 as a reference; (a) There are three types of punishments imposed on disciplinary ASN which fall into the light discipline category, namely in the form of an oral warning, a written warning, and a written statement of dissatisfaction; (b) The imposition of disciplinary sanctions while accepting bribes by ASN and ASN officials who commit acts of domestic violence is not in accordance with PP No. 94 2021 and still refers to PP No. 53 of 2010 due to the imposition of sanctions in the form of demotion to a lower level for 1 year and postponement of promotion for one year included in the category of severe disciplinary punishment; (c) The imposition of sanctions or the establishment of severe disciplinary punishment in the Bengkulu city government area already refers to Government Regulation No. 94 of 2021, namely the imposition of punishments in the form of; demotion to a lower level for 12 months, release from position as executor for 12 months, and honorable discharge not at his own request.; (2) Obstacles in the implementation of disciplinary ASN development in the work environment of the Bengkulu city government, namely the enforcement of discipline against civil servants (ASN) are considered not to be carried out optimally. One of these conditions is the result of the enactment of Government Regulation (PP) Number 53 of 2010 concerning ASN Discipline in the Bengkulu City Government, where this PP has not explicitly and in detail regulated ASN discipline. The implementation of these technical regulations is still far from expectations. Moreover, it is very dependent on the subjectivity of staffing supervisors (PPK).